How did you get this answer. Can you show the steps?

Question

Asked 5/3/2013 12:06:53 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

s

Expert answered|debnjerry|Points 46601|

Expert answered|debnjerry|Points 46601|

Question

Asked 5/3/2013 12:06:53 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

There are no new answers.

Solve the following system of equations, using the graphing method:
x + 2y = 4
2x - y = 3

Question

Not Answered

Updated 10/1/2014 6:22:14 AM

1 Answer/Comment

The solutions for the systems x + 2y = 4, 2x - y = 3 are x = 2, y = 1.

Multiply x + 2y = 4 by -2:

-2x - 4y = -8;

(-2x - 4y = -8) + (2x - y = 3):

-5y = -5;

y = 1;

Solve for x:

x + 2(1) = 4;

x + 2 = 4;

x = 4 - 2;

x = 2

Multiply x + 2y = 4 by -2:

-2x - 4y = -8;

(-2x - 4y = -8) + (2x - y = 3):

-5y = -5;

y = 1;

Solve for x:

x + 2(1) = 4;

x + 2 = 4;

x = 4 - 2;

x = 2

Added 10/1/2014 6:22:14 AM

This answer has been confirmed as correct and helpful.

Solve the following system of equations: x + 2y = 4 2x - y = 3 Here are the multiple choices: (2, 1) (-1, -3) (0, 4) (5, -2)

Question

Not Answered

Updated 3/1/2015 2:59:43 AM

1 Answer/Comment

The solution set for the systems x + 2y = 4, 2x - y = 3 is: (2, 1)

(x + 2y = 4) * (-2);

-2x - 4y = -8;

(-2x - 4y = -8) + (2x - y = 3);

-5y = -5;

y = 1;

x + 2 = 4;

x = 4 - 2;

x = 2

(x + 2y = 4) * (-2);

-2x - 4y = -8;

(-2x - 4y = -8) + (2x - y = 3);

-5y = -5;

y = 1;

x + 2 = 4;

x = 4 - 2;

x = 2

Added 3/1/2015 2:59:43 AM

This answer has been confirmed as correct and helpful.

Solve the following system of equations, using the elimination method: 5x + 3y = -7 7x - 3y = 55
**Weegy:** Solve the following system of equations, [ using the elimination method: 5x + 3y = -7 7x - 3y = 55
Answer 5x + y = -17 - - - > 15x + 3y = -51 {multiplied top equation by 3}
7x - 3y = -37
15x + 3y = -51 {new top equation}
7x - 3y = -37 {original bottom equation}
- - - - - - -
22x = -88 {added the two equations together}
x = -4 {divided both sides by 22}
5x + y = -17 {top equation}
5(-4) + y = -17 {substituted -4, in for x, into top equation}
-20 + y = -17 {multiplied 5 by -4}
y = 3 {added 20 to both sides}
x = -4 and y = 3
Source ] **User:** Here are the multiple choices: (4, -9)
(3, -6)
(0, -14)
(7, 3) (More)

Question

Expert Answered

Updated 6/23/2014 10:41:41 PM

1 Answer/Comment

5x + 3y = -7

7x - 3y = 55

adding up equations the result is:

12x = 48

x = 48/12 = 4

5(4) + 3y = -7

20 + 3y = -7

3y = -7 - 20 = -27

y = -27/3 = -9

The solution for the system 5x + 3y = -7 7x - 3y = 55 is (4, -9)

7x - 3y = 55

adding up equations the result is:

12x = 48

x = 48/12 = 4

5(4) + 3y = -7

20 + 3y = -7

3y = -7 - 20 = -27

y = -27/3 = -9

The solution for the system 5x + 3y = -7 7x - 3y = 55 is (4, -9)

Added 6/23/2014 10:41:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/23/2014 11:34:32 PM]

Is there an expert that can help me with this probem? **Weegy:** Yes, What is the problem? **User:** **User:** Simplify the exponential expression. (12x-3y-2z3)-² over (3xy-2z-3) **Weegy:** 32 Expert answered|Moja2013|Points 50| **User:** That's incorrect! Here are the multiple choices: x4over 16z12, x8 over 16z12, 4x8 over z12, x8y4 over 16z12 **Weegy:** 32 32 Expert answered|iamsuperman28|Points 0| **User:** That's incorrect. Please look at the multiple choices. (More)

Question

Expert Answered

Asked 5/3/2013 10:19:40 AM

0 Answers/Comments

Perform the indicated operations. Write the resulting polynomial in standard form.
(9x^4 + 2x^3 + 6x^2 - 6) - (5x^4 + 7x^3 + 3x^2 + 3). Here are the multiple choices: 4x4 - 5x3 + 3x2 - 9,
14x4 + 9x3 + 9x2 - 3,
14x4 + 9x3 + 9x2 - 9,
4x4 + 9x3 + 9x2 - 3, **Weegy:** (9x^4 + 2x^3 + 6x^2 - 6) - (5x^4 + 7x^3 + 3x^2 + 3) = 4x^4 -5x^3 + 3x^2 -9 (More)

Question

Expert Answered

Updated 9/17/2015 8:03:04 AM

0 Answers/Comments

35,205,531

questions answered

There are no comments.